A novel method for cellulose modification in aqueous media via alkoxysilane chemistry - Fereshteh Fadavi; Ali Abdolkhani; Yahya Hamzeh; Hubert Hettegger; Thomas Rosenau (Iranian Journal of Wood and Paper Industries, 2016)
Surface modification of cellulose, as the world’s most abundant polymer, plays an important role in sustainable chemistry. Microcrystalline cellulose, Avicel, was modified by an alkoxysilane under mild conditions in water, at room temperature and with a catalytic amount of sodium hydroxide. (3-Mercaptopropyl)-trimethoxysilane in three concentrations 535, 1074, 1614 µmol/mL (100, 200, 300 µL of silane, respectively) was grafted onto cellulose, then the modified cellulose was characterized by FTIR spectroscopy as well as solid state 13C NMR and 29Si NMR spectroscopy. Increasing the concentration of the alkoxysilane from 353 to 1074 µmol/mL increased the ratio of siloxane bridges with the cellulose backbone, while by increasing the silane concentration from 1074 to 1614 µmol/mL, has inhanced the ratio of polysiloxane bridges relative to covalent links with the cellulose backbone from 34% to 66%.